2018
DOI: 10.1101/249532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extensive genomic diversity among Mycobacterium marinum strains revealed by whole genome sequencing

Abstract: 33Mycobacterium marinum is the causative agent for the tuberculosis-like disease 34 mycobacteriosis in fish and skin lesions in humans. Ubiquitous in its geographical 35 distribution, M. marinum is known to occupy diverse fish as hosts. However, information 36 about its genomic diversity is limited. Here, we provide the genome sequences for 15 M. 37 marinum strains isolated from infected humans and fish. Comparative genomic analysis of 38 these and four available genomes of the M. marinum strains M, E11, MB2 a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Recent advances in genome sequencing technology have enabled the comparison of clinically-isolated strains at the whole genome level and this has revealed that some mycobacterial species have open pan-genomes [6][7][8][9]. In M. avium, the genomic diversity is classified into several subspecies, including subspecies avium, hominissuis, paratuberculosis, and silvaticum [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in genome sequencing technology have enabled the comparison of clinically-isolated strains at the whole genome level and this has revealed that some mycobacterial species have open pan-genomes [6][7][8][9]. In M. avium, the genomic diversity is classified into several subspecies, including subspecies avium, hominissuis, paratuberculosis, and silvaticum [10].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, another Tn-Seq conducted on the M. marinum E11 strain showed only 6% of essential genes (Weerdenburg et al, 2015). The difference between the two studies is probably due to their genomic diversity, a recent comparative genomic analysis revealed that M. marinum strains should be divided into two different clusters, the "M"-and the "Aronson"-type (Das et al, 2018). Among the essential genes identified in M. marinum M, 237 orthologues were found in M. marinum E11 (37.3%) (Weerdenburg et al, 2015), and 311 orthologues in M. tuberculosis (44.4%) (DeJesus, Gerrick, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%